Pemigatinib in Intrahepatic Cholangiocarcinoma: A Work in Progress - Gennaro Gadaleta-Caldarola; Alessandro Rizzo; Vincenzo Dadduzio; Lucia Lombardi; Arianna Gadaleta-Caldarola; Stefania Infusino; Antonio Cusmai; Claudia Citrigno; Gennaro Palmiotti (Current Oncology, 2022)
Cholangiocarcinoma (CCA) is the second most frequent primary liver cancer, following hepatocellular carcinoma (HCC). Progress in the molecular understanding of CCA has led to the development of several agents, including FGFR inhibitors, such as pemigatinib, whose approval has marked a new era in this hepatobiliary malignancy. However, a number of questions remain unanswered, including the development of secondary resistance and the role of combination therapies, including FGFR inhibitors. Herein, we specifically focus on the current challenges and future research directions of pemigatinib use in CCA patients.